EVALUATION OF SELF-HARM AND SUICIDAL ATTEMPTS AMONG UNIVERSITY STUDENTS - SIYAL, FJ; JISKANI, SA; SUNIL, R; ALI, A; BUGHIO, N; BULEDI, A; SHAIKH, B; ABBAS, W; SIYAL, S; SHAIKH, ZA; et al. (Biological and Clinical Sciences Research Journal, 2023)
Self–harm and suicidal attempts are very important public health concerns and emerging issues affecting millions globally, especially young and adults. Suicidal attempts and self–harm are essential predictors of suicide in future and intolerable suffering. Assessment in this domain is challenging as no agreement is observed to conceptualize the behaviors. Our study aims to assess the prevalence rate of suicidal attempts and thoughts and self–harm thoughts in young adults. This cross-sectional study was conducted at Shaheed Mohtarma Benazir Bhutto Medical University for 6 months. An online questionnaire was prepared and circulated among young adults. Informed consent was obtained from all participants. The questionnaire included many demographic questions, including age, gender, living status, and relationship status. The data was analyzed using SPSS 24.0. For all qualitative variables, frequencies and percentages were measured. A total of 401 responses were collected. The number of female participants was more (66.6%) than male participants (33.4%). The majority of participants (70.3%) were aged between 18-23 years, followed by 24-29 years (23.7%) and 30-35 years (6%). In questions regarding self–harm and suicidal thoughts, 27.2% of respondents said that they had serious thoughts about suicide but never attempted it, 17.2% responded that they had such thoughts before attending university, and 11.7% said that they tried to attempt suicide in some manner. Thoughts of suicide and self–harm were observed among university students. Various factors influence students’ mental health, including parental help, home environment, and university workload. Stress–free environment and social support to students may decrease the prevalence of suicidal tendencies among students.